All‐Climate Stretchable Dendrite‐Free Zn‐Ion Hybrid Supercapacitors Enabled by Hydrogel Electrolyte Engineering. Issue 2 (22nd April 2022) - Jiang, Yuqi; Ma, Kun; Sun, Meiling; Li, Yuanyuan; Liu, Jinping
Abstract : Hybrid supercapacitors have shown great potentials to fulfill the demand of future diverse applications such as electric vehicles and portable/wearable electronics. In particular, aqueous zinc‐ion hybrid supercapacitors (ZHSCs) have gained much attention due to their low‐cost, high energy density, and environmental friendliness. Nevertheless, typical ZHSCs use Zn metal anode and normal liquid electrolyte, causing the dendrite issue, restricted working temperature, and inferior device flexibility. Herein, a novel flexible Zn‐ion hybrid supercapacitor (FZHSC) is developed by using activated carbon (AC) anode, δ‐MnO2 cathode, and innovative PVA‐based gel electrolyte. In this design, heavy Zn anode and its dendrite issue are avoided and layered cathode with large interlayer spacing is employed. In addition, flexible electrodes are prepared and integrated with an anti‐freezing, stretchable, and compressible hydrogel electrolyte, which is attained by simultaneously using glycerol additive and freezing/thawing technique to regulate the hydrogen bond and microstructure. The resulting FZHSC exhibits good rate capability, high energy density (47.86 Wh kg −1 ; 3.94 mWh cm −3 ), high power density (5.81 kW kg −1 ; 480 mW cm −3 ), and excellent cycling stability (~91% capacity retention after 30 000 cycles). Furthermore, our FZHSC demonstrates outstanding flexibility with capacitance almost unchanged even after various continuous shape deformations. The hydrogel electrolyte still maintains high ionic conductivity at ultralow temperatures (≤−30°C), enabling the FZHSC cycled well, and powering electronic timer robustly within an all‐climate temperature range of −30~80°C. This work highlights that the promising Zn metal‐free aqueous ZHSCs can be designed with great multifunctionality for more practical application scenarios. Abstract : An advanced quasi‐solid‐state flexible Zn‐ion hybrid supercapacitor (FZHSC) is developed in the absence of heavy Zn, avoiding the growth of Zn dendrite. Enabled by the anti‐freezing, stretchable, and compressible PVA hydrogel electrolyte designed via hydrogen bond and microstructure regulation, the FZHSC exhibits robust stretchability and can be operated at −30~80 °C, ensuring all‐climate application.